La calidad y servicios turísticos en la Parroquia de Salinas de Guaranda, Provincia de Bolívar - López Orozco, Gehova Karina (2019)
The proposed topic was "The Quality and Tourist Services in Salinas de Guaranda Parish, Bolivar Province.' With prior analysis, it was determined that the inadequate Quality and Tourist Services in Salinas de Guaranda Parish, causes problems in the tourist area. The general objective was to identify how quality influences the tourist services offered in Salinas de Guaranda Parish. The specific objectives were: Identify how empathy influences the tourist services offered in Salinas de Guaranda Parish, Bolívar Province. Identify how security influences the tourist services offered in Salinas de Guaranda Parish, Bolívar Province. Identify how the response capacity influences the tourist services offered in Salinas de Guaranda Parish, and develop a Tourism Quality Program for the Providers of Services of Salinas de Guaranda. The theoretical framework was developed concerning the two study variables: the methodology applied was through the SPSS program. The population was twenty-nine service providers of the parish, according to the tourist cadaster that was obtained from the CTC people over 18 years old. Nineteen thousand tourists, who arrived at the parish in 2018 were taken into account. A projection was made for the year 2019 from January to May corresponding to 7,917 tourists, with 1,583 tourists per month. Finally, it was concluded that it is essential to carry out a Tourism Quality Program for the Providers of Services of Salinas de Guaranda, to standardize all the processes of Tourist Services provision and adapt it to the needs of tourists.